Corruption and the performance of small and medium-sized enterprises in Gauteng - Chetty, Melanie (University of the Witwatersrand, Johannesburg, 2024)
In most countries SMEs are vital to economic advancement and sustainability of small businesses are critical to a nation`s socioeconomic stability; otherwise, the country faces stagnation in its economy. Corruption is a global challenge which threatens sustainable economic development and adherence to good governance creates an environment where corruption struggle to flourish. this study examine the impact of corruption on SMEs in Gauteng using a quantitative research methodology whereby 77 respondent were located in Gauteng.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Corruption; Small and medium enterprises; Anti-corruption measures; Gauteng; Bribery acts; UCTD; SDG-8: Decent work and economic growth